2015
DOI: 10.1016/j.ajog.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry juice capsules and urinary tract infection after surgery: results of a randomized trial

Abstract: Objective The risk of urinary tract infection (UTI) among women undergoing elective gynecologic surgery where a catheter is placed is high: 10 to 64% following catheter removal. We conducted the first randomized, double-blind, placebo-controlled trial of the therapeutic efficacy of cranberry juice capsules in preventing UTI post surgery. Study Design We recruited patients from a single hospital between August 2011 and January 2013. Eligible participants were undergoing elective gynecologic surgery that did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 16 publications
2
64
4
5
Order By: Relevance
“…Recently, Foxman et al . published the results of a randomised controlled trial that, similar to our study, aimed to assess the efficacy of cranberry capsules in preventing UTI after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Foxman et al . published the results of a randomised controlled trial that, similar to our study, aimed to assess the efficacy of cranberry capsules in preventing UTI after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study among women undergoing elective gynecological surgery with urinary catheter removal showed that two cranberry capsules twice per day (equivalent to 16 ounces of cranberry juice) over six weeks were able to reduce the rate of UTI by half. 31 However, all participants were instructed to drink 8 ounces of water twice a day with each capsule administration so it is possible that the fluid load was necessary along with cranberry product. Hydration may also be a necessary component to reduce bacteriuria and urinary symptoms in older women.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have showed the beneficial effects of cranberry intake on human health [1,2,3,4,5,6,7]. However, while in vitro studies have shown dose-response effects of cranberry (poly)phenols on the inhibition of microbial invasion of gut and bladder epithelial cells [8,9] and in the cytotoxicity of ovarian cancer cells [10], very few human dose-response studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%